Plant-derived antimalarial agents: from crude extracts to isolated bioactive compounds - Abdullah, Wan Omar; Ismail, Patimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Despite decades of intense research, malaria remains a deadly disease of the developing worlds. Drugresistance to limited available antimalarials, in part, has contributed to the persistence of this infectious disease. Likewise, the use of antimalarials such as artemisinin, though effective in global malaria control programs, is hampered by high cost and limited supply. Therefore, identification of an antimalarial drug that is easy to isolate and produce, inexpensive, and demonstrates little toxicity across a diverse population represents the ideal agent needed for global malaria control programs and eradication of this deadly disease. This review discusses several antimalarial compounds containing unique structural composition that have been isolated and characterized from plant sources. These compounds have exhibited promising antimalarial activities in vitro and in vivo. However, limitations such as toxicity, low bioavailability and/or poor solubility have probably restricted the scope of use for several plant products in humans. Nevertheless, plants provide novel leads, which can be developed into safe drugs by synthetic strategies as exemplified by artemether and quinoline class of antimalarials. Therefore, plant bioactive compounds described herein provide useful alternatives, which could be modulated to obtain antimalarials active against not only drug-sensitive, but also drug-resistant and multi-drug resistant strains of Plasmodium. In this direction, semi synthetic approaches to newer and modified antimalarials have provided useful insights into their applicability in antimalarial drug discovery.